THEORETICAL, ECONOMIC AND METHODOLOGICAL BASIS OF PROPERTY INSURANCE (American Journal of Business Management, Economics and Banking, 2024)
In this article, the theoretical, economic, and methodological foundations of property insurance, as well as suggestions and practical recommendations for the implementation of property insurance relations and further improvement of insurance relations have been developed.